Serum proteomic characterization of stump-tailed macaques (Macaca arctoides) with neutralizing antibodies against Dengue virus in Thailand - Pakorn Ruengket; Sittiruk Roytrakul; Daraka Tongthainan; Kobporn Boonnak; Kanokwan Taruyanon; Bencharong Sangkharak; Wirasak Fungfuang (PLoS ONE, 2026)
Dengue infection is a leading global public health problem, and the virus (DENV) is transmitted by Aedes mosquitoes and causes a wide spectrum of clinical manifestations in humans. Previous studies have shown that wild macaques in Thailand have been exposed to the dengue virus. Accordingly, this study aims to characterize the serum proteomic profiles of wild macaques with (seropositive) and without (naive) dengue virus-neutralizing antibodies, to improve our understanding of differential protein expression and identify candidate biomarkers. We analyzed thirty-two serum samples obtained from wild macaques in Thailand. Out of the 32 samples, 16 macaques (50%) were seropositive for DENV. A total of 9,532 proteins were identified, out of which 582 were differentially expressed (DEPs) and used to generate a proteomic profile. Among the nine identified proteins of interest, three were associated with the nervous system, while the remaining six have been reported to play roles in anti-dengue antiviral mechanisms. These include the induction of interferon responses triggered by cellular stress, degradation of viral RNA, and activation of dendritic cells and Th1-mediated immune responses via IFN-γ and TNF-α. Although these proteins have been implicated in the nervous system and are involved in anti-DENV in several reports, in this study, it was shown that these proteins remain up-regulated even after infection, which requires further study into the dynamics after long-term infection in the future. These findings highlight the need for further longitudinal studies to validate the functional relevance of these proteins.